TRANSFORMATIVE LEARNING MODEL FOR PARENTING EDUCATION PROGRAM - Frimha Purnamawati; Rizqi Fajar Pradipta (Kopertis Region IV Jabar and Banten, 2022)
The purpose of this study is to produce a transformative learning model in parenting education programs organized by early childhood education institutions in changing the terms of reference for children's education to be even better and in synergy with those carried out by educational institutions. This research includes development model research. The results of this study are a transformative learning model in a parenting education program that uses five components, namely (1) syntax; (2) Social System; (3) Reaction Principle; (4) Support System and (5) Instructional Impact and Accompaniment. The steps of Transformative Learning used in the parenting education process consist of 4 steps of field activities, namely: (1) problem development steps; (2) critical reflection development steps; (3) location of determination and implementation of action; and (4) assistance steps taken by educators of early childhood education institutions to early childhood parents in the form of consultations, group discussion activities, and face-to-face activities (class sessions). The success of transformative learning in this parenting education program is that there is a change in the frame of reference of the parents of early childhood which comes from themselves, and the function of educators in this transformative learning process is as a facilitator and counselor in helping towards the change process.